KOMPONEN KIMIA KAYU TRUBUSAN JATI UNGGUL NUSANTARA (Tectona grandis Linn.f.) PADA BAGIAN PANGKAL, TENGAH DAN UJUNG - Fathia Maulida; Kustin Bintani Meiganati; Mamay Maslahat (JURNAL SAINS NATURAL, 2020)
Chemical Component of Copies Superior Teak (Tectona grandis Linn.f)in Base, Center and Edge StemTeak (Tectona grandis, Linn. f) is one of the plants that is able to make a real contribution in providing wood raw materials in the timber industry. The limited availability of quality teak wood on the market so that the craftsmen use superior teak wood. The amount of the superior teak wood has not been known yet. Therefore, a study was carried out on the level of wood chemical components of five-year-old superior teak wood based on the height of the stem (base, middle and end), so that the suitability of wood usage can be known. Based on the results of the study the levels of chemical components in wood superior teak of age five years, the highest levels of extractive substances found at the end of the stem by 8.56%, the highest percentage of levels of holocellulose and cellulose found in the middle part of the stem with a content of 63.95% and 39.99%, the percentage of hemicellulose content 29.66% and the highest percentage of lignin content found in the base part with levels of 30.52%. This superior teak wood can be used as construction materials such as plywood, woodworking wood, lamina wood and artificial boards.Keyword: Tectona grandis, Thrubus, Extractive Subtances, Holocellulose, Cellulose, Lignin.ABSTRAKTanaman Jati (Tectona grandis, Linn. f) merupakan tanaman yang berkontribusi di bidang industri perkayuan. Terbatasnya ketersediaan kayu jati berkualitas di pasaran mengakibatkan industri perkayuan menggunakan kayu jati unggul. Kayu trubusan jati unggul tersebut belum diketahui bagaimana komponen kimianya. Oleh karena itu, dilakukan penelitian mengenai kadar komponen kimia kayu trubusan jati unggul yang berumur lima tahun berdasarkan ketinggian batang (pangkal, tengah dan ujung), sehingga dapat diketahui kesesuaian penggunaan kayu. Berdasarkan hasil penelitian kadar komponen kimia pada kayu trubusan jati unggul umur lima tahun, rata-rata kadar zat ekstraktif tertinggi terdapat pada bagian ujung batang sebesar 8,56%, persentase tertinggi kadar holoselulosa dan selulosa terdapat pada bagian tengah batang dengan kadar 63,95% dan 39,99%, persentase kadar hemiselulosa 29,66%, dan persentase tertinggi kadar lignin terdapat pada bagian pangkal dengan kadar 30,52%. Kayu trubusan jati unggul ini dapat digunakan sebagai bahan konstruksi seperti kayu lapis, kayu pertukangan, kayu lamina dan papan buatan.Kata Kunci: Tectona grandis, Thrubus, Zat Ekstraktif, Holoselulosa, Selulosa, Lignin.